Berberine Reverses Breast Cancer Multidrug Resistance Based on Fluorescence Pharmacokinetics In Vitro and In Vivo - Qian, Ke (ACS Omega, 2021)
[Image: see text] Exploring the mechanism through which berberine (Ber) reverses the multidrug resistance (MDR) of breast cancer is of great importance. Herein, we used the methyl thiazolyl tetrazolium assay to determine the drug resistance and cytotoxicity of Ber and doxorubicin (DOX) alone or in combination on the breast cancer cell line MCF-7/DOX(Fluc). The results showed that Ber could synergistically enhance the inhibitory effect of DOX on tumor cell proliferation in vitro, and the optimal combination ratio was Ber/DOX = 2:1. Using a luciferase reporter assay system combined with the bioluminescence imaging technology, the efflux kinetics of d-luciferin potassium salt in MCF-7/DOX(Fluc) cells treated with Ber in vivo was investigated. The results showed that Ber could significantly reduce the efflux of d-luciferin potassium salt in MCF-7/DOX(Fluc) cells. In addition, western blot and immunohistochemistry experiments showed that the expression of P-glycoprotein (P-gp/ABCB1) and multidrug resistance protein 1 (MRP1/ABCC1) in MCF-7/DOX(Fluc) cells was downregulated upon Ber treatment. Finally, high-performance liquid chromatography was used to investigate the effect of Ber on DOX tissue distribution in vivo, and the results showed that the uptake of DOX in tumor tissues increased significantly when combined with Ber (P < 0.05). Thus, the results illustrated that Ber can reverse MDR by inhibiting the efflux function of ATP-binding cassette transporters and downregulating their expression levels.